Tunable Superhydrophobicity from 3D Hierarchically Nano‐Wrinkled Micro‐Pyramidal Architectures. (10th April 2021) - Zhang, Weixin; Gao, Jie; Deng, Yujun; Peng, Linfa; Yi, Peiyun; Lai, Xinmin; Lin, Zhongqin
Abstract: Interfacial surfaces with hierarchical structures have triggered intense research interest and been used in a broad range of applications ranging from anti‐icing, anti‐fogging, surface‐enhanced Raman spectroscopy to catalytic reaction. However, the high‐cost manufacturing processes and the limited durability remain as great challenges that need to be addressed, especially for superhydrophobicity. In this work, a novel hybrid approach for stretchable, transparent, and robust superhydrophobic surfaces is proposed, constructing micro‐pyramid architectures with tunable hierarchical wrinkles efficiently and in an environmentally friendly manner. Due to the multiscale structures, excellent superhydrophobicity is obtained with contact angle of ≈172° and sliding angle ≈5° in a steady "Lotus" state. Further, the wear resistance and stability tests also suggest a superior performance under simulated severe real‐world applications. Utilizing such multiscale synergistic co‐operation effects can be an excellent manufacturing strategy and be extended to other surface engineering where hierarchical architectures are needed. Abstract : Micro‐pyramid arrays with wrinkled nano‐structures for robust and high‐performance superhydrophobicity are realized through a hybrid approach of molding and plasma‐assisted surface instability. The micro‐scale structures play a crucial role for mechanical stability and the programmable nano‐scale wrinkles are conducive to regulate the surface wetting state. The hierarchical structures exhibit an apparent contact angle and sliding angle of 172° and 5°, respectively.